Efecto del uso de Saccharomyces cerevisiae en procesos de fermentación de cacao (Theobroma cacao L.), clon CNN51 y su influencia en la calidad - Erazo Rocillo, Jherman Vinicio (2024)
The cacao is of great importance in the country because its production and commercialization benefit many families. However, the quality of this product is significantly influenced by post-harvest practices, which are crucial for developing attributes to produce quality chocolate. The present study was carried out at the Quinta Experimental La Argelia of the National University of Loja, under a Completely Randomized Design (CRD) with 12 treatments and 3 replications. The relevance of this study focused on the relationship between yeast application, washing and fermentation time, and how these factors influence the quality attributes in the organoleptic analysis of cocoa clone CNN5. To carry out the research, the harvest was carried out in the canton of Palanda, province of Zamora Chinchipe, and then the fermentation process was carried out at the National University of Loja. The behavior of 3 doses (0 g, 0.4 g and 0.6 g) of Saccharomyces cerevisiae were evaluated; it was applied in two times of 3 and 5 days in anaerobic fermentation; after the fermentation process, 6 treatments were washed until the mucilage was removed from the almonds. The pH and °Bx variables were evaluated at the beginning and at the end of fermentation; a cut-off test was performed to determine the percentage of fermentation. In the results obtained it was observed that the decreasing trend of the variables (pH and °Bx) was a function of dose and time, the most notable reduction in pH and °Bx was observed at the dose of 0.6 g at both times. With respect to the cut test, fermentation percentages greater than 75% were obtained. Sensory analysis was carried out at INIAP's Pichilingue Tropical Experimental Station, where basic flavors (astringency, bitterness and acidity), specific flavors (cocoa, nut, fresh fruit, floral, spices, brown fruit, vegetable, wood and caramel) and defective flavors were evaluated. Pronounced cocoa flavors were obtained in all treatments; T5 acquired floral and caramel flavors, while T12 presented particularities in nutty flavor. It is concluded that the addition of Saccharomyces cerevisiae had a positive influence in improving the organoleptic characteristics of cocoa, providing flavors that can guarantee cocoa quality.